Improving the legal framework for improving the activities of the Chamber of Advocates of the Republic of Uzbekistan - Abdijemilova , Sholpanay (INTERNATIONAL CONFERENCE ON MODERN RESEARCH AND SCIENTIFIC INNOVATION, 2026)
This thesis is devoted to the analysis of legal and institutional ways to improve the activities of the Chamber of Advocates in the development of the institute of the Bar in the Republic of Uzbekistan. The study covers the legal status, powers of the Chamber of Advocates and the problems associated with the implementation of the principle of self-government.